PENGARUH AGENCY COSTS TERHADAP DIVIDEND PAYOUT RATIO (Studi Pada Perusahaan Manufaktur Listed Di BEI Tahun 2009-2011) - Arifin, Zainul; Ratnawati, Kusuma (Jurnal Ilmiah Mahasiswa FEB, 2013)
This study aims to determine the effect of agency costs that proxied insider ownership, institutional ownership, collateralizable assets, debt to total assets, and firm size on dividend payout ratio. This study uses multiple linear regression model on the 13 companies sample’s that listed on the Indonesia Stock Exchange (BEI) in 2009-2011. The study found the evidence of the variable insider ownership, institutional ownership, collateralizable assets, debt to total assets, and firm size simultaneously affect on the dividend payout ratio. In partial, the variable of institutional ownership and collateralizable assets has positive effect and significant, while the variable of insider ownership and firm size has negative effect and insignificant, and variable of debt to total assets has positive effect and insignificant on dividend payout ratio. Forming variable costs of the agencies that most dominant on the company’s dividend payout ratio is collateralizable assets. Keyword : agency costs, insider ownership, institutional ownership, collateralizable assets, debt to total assets, firm size, dan dividend payout ratio.